The Impact of AI Application on Customers and Employees in Auto-Detailing Business - Soonthornson, Phitsinee; Apibunyopas, Preeyanuch (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
The objective of this research is to explore the impact of technology acceptance on both customer satisfaction and employee efficiency in the auto-detailing business, using Wisdom Car Detailing, a car detailing service located in Bangkok, as a case study. By using a mixed-method approach, quantitative data were collected through structured questionnaires and analyzed using multiple regression analysis, and qualitative data were collected from interviews with their employees. Technology acceptance has a strong positive correlation with customer satisfaction and employee efficiency. Post-AI integration, 85% of customers have agreed that their experiences have improved, and further studies have suggested that success in training employees and organizational innovativeness can enhance service quality and overall organizational performance. Article history: Accepted 14 March 2025 Revised 17 April 2025 Accepted 19 April 2025 SIMILARITY INDEX = 0.00 %......